2021
DOI: 10.3390/ph14080767
|View full text |Cite
|
Sign up to set email alerts
|

β-Cells Different Vulnerability to the Parkinsonian Neurotoxins Rotenone, 1-Methyl-4-phenylpyridinium (MPP+) and 6-Hydroxydopamine (6-OHDA)

Abstract: Neurotoxins such as rotenone, 1-methyl-4-phenylpyridinium (MPP+) and 6-hydroxydopamine (6-OHDA) are well known for their high toxicity on dopaminergic neurons and are associated with Parkinson’s disease (PD) in murine models and humans. In addition, PD patients often have glucose intolerance and may develop type 2 diabetes (T2D), whereas T2D patients have higher risk of PD compared to general population. Based on these premises, we evaluated the toxicity of these three toxins on pancreatic β-cell lines (INS-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(76 reference statements)
3
1
0
Order By: Relevance
“…The IC 50 values of rotenone and thapsigargin were determined as 30 nM and 22 nM, respectively, and were used as final treatment conditions of INS-1 832/13 cells in this study. The IC 50 value of rotenone agreed with previously reported results of the same cell type, 27 while that of thapsigargin was reported as ∼4 μM in the SW-13 and NCI-H295R cell lines. 28 Clearly the IC 50 of thapsigargin is cell line dependent, which reflects each cell line's potential vulnerability to stress.…”
Section: ■ Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The IC 50 values of rotenone and thapsigargin were determined as 30 nM and 22 nM, respectively, and were used as final treatment conditions of INS-1 832/13 cells in this study. The IC 50 value of rotenone agreed with previously reported results of the same cell type, 27 while that of thapsigargin was reported as ∼4 μM in the SW-13 and NCI-H295R cell lines. 28 Clearly the IC 50 of thapsigargin is cell line dependent, which reflects each cell line's potential vulnerability to stress.…”
Section: ■ Resultssupporting
confidence: 91%
“…The IC 50 value of rotenone agreed with previously reported results of the same cell type, while that of thapsigargin was reported as ∼4 μM in the SW-13 and NCI-H295R cell lines . Clearly the IC 50 of thapsigargin is cell line dependent, which reflects each cell line’s potential vulnerability to stress …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We showed that the addition of 1 μM rotenone to freshly isolated mitochondria led to the complete loss of mitochondrial displacement activity. This loss of activity is most likely due to the toxicity of rotenone as reported in numerous studies (Giordano et al, 2012;Siddiqui et al, 2013;Bavli et al, 2016;Frye et al, 2016;Carli et al, 2021). In addition, our results are in line with a previous study using the AFM-based nanomotion method (Stupar et al, 2017).…”
Section: Discussionsupporting
confidence: 92%